2021
DOI: 10.1177/19418744211037319
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Diagnosis and Treatment of Bacterial Meningitis in NYC: Retrospective Cohort Analysis

Abstract: Community-acquired bacterial meningitis (CABM) morbidity and mortality remains high in those infected. Rapid diagnosis and treatment is paramount to reducing mortality and improving outcome. This retrospective cohort study aims to assess the time from presentation to diagnosis and treatment of vaccine preventable CABM as well as identify possible factors associated with delays in diagnosis and antibiotic administration. A retrospective chart review was conducted of individuals who presented to Columbia Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…We also observed that 5% of SAH and 18% of bacterial meningitis cases were possibly misdiagnosed at index ED visits, estimates which are consistent with prior literature . Although we did not observe a significant change in the proportion of missed diagnoses over time, the small number of cases limited detection of differences.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that 5% of SAH and 18% of bacterial meningitis cases were possibly misdiagnosed at index ED visits, estimates which are consistent with prior literature . Although we did not observe a significant change in the proportion of missed diagnoses over time, the small number of cases limited detection of differences.…”
Section: Discussionsupporting
confidence: 90%
“…Another conceivable theory is an underdiagnosis among the younger population due to refraining from visiting hospitals during the pandemic, especially among those with mild and self-remitting symptoms of viral meningitis. An underdiagnosis of cases of acute meningitis, if present, could thus be considered to be a negative aspect associated with the pandemic, as a delayed lumbar puncture was shown to be associated with increased medical costs and higher mortality rates (20,21). Therefore, both the actual decrease in the prevalence of acute meningitis and possible underdiagnosis due to refraining from visiting hospitals among mild cases could have contributed to the dramatic decrease in the number of hospitalized cases of acute meningitis during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to this problem is that obtaining CSF analysis by lumbar puncture in children is dependent on parental approval with high refusal rates documented in Iraq [6]; this together with the lack of confirmation of cases of meningitis has led to underreporting of the cases in Iraq [5]. Meningitis is prevalent in the pediatric age group and undiagnosed cases or delays in the diagnosis can lead to a high mortality rate [7][8][9]. This all calls for a need to find a constellation of clinical presentations and hematological indices to serve as a diagnostic tool or at least for screening febrile children during meningitis outbreaks for early case identification and management.…”
Section: Introductionmentioning
confidence: 99%